825. CORYLUS FARGESII: A rare tree‐forming hazel, with exfoliating bark Corylaceae. (22nd April 2016) - Aiello, Anthony S.
Summary: Corylus fargesii (Franch.) C.K. Schneid. from western China is illustrated with a hand‐coloured engraving; its introduction, horticultural merits and cultivation are discussed.